A Review on Solar Tracking System (International Journal of Innovative Research in Engineering & Management, 2021)
Review of a solar tracking system the greatest problem for the  next half-century will be generating electricity from the decrease  of fossil fuels. When compared to other renewable energy  sources, the concept of turning solar energy into electrical energy using photovoltaic panels is at the top of the list.  However, the sun's relative angle is always changing. The  number of watts supplied by a solar panel is reduced when  measured in relation to the earth. In this case, a solar tracking  system is used. The most efficient way to boost the efficiency  of a solar panel. The payload is moved using solar trackers  during the day, towards the sun. Different kinds of tracking  systems are discussed in this article. Their advantages and  disadvantages are thoroughly addressed. The findings of this  study show that the azimuth is correct. In comparison to other  tracking systems, the altitude dual axis tracking system is more  efficient. However, in the standpoint of cost and flexibility a single-axis tracking system is more practical than a dual-axis  system.
Keywords: Azimuth; Passive Actuator; Photovoltaic Pane; Solar Energy; Solar Tracker